How the Populist Radical Right Transformed Swiss Welfare Politics: From Compromises to Polarization. Issue 4 (9th October 2015) - Afonso, Alexandre; Papadopoulos, Yannis
Abstract: This paper shows how the rise of the Swiss People's Party (SVP) has affected welfare state reforms in Switzerland between the 1990s and the 2000s. In the 1990s, welfare state reforms drew on "modernizing" coalitions between FDP (Liberals), CVP (Christian Democrats) and SP (Social Democrats) combining retrenchment and "recalibration". In the 2000s the FDP and CVP increasingly sided with the SVP in right‐wing coalitions pushing retrenchment alone. The article shows that changes in party competition have affected welfare schemes differently, with a policy gridlock in pension reforms, where voters of the SVP do not follow their elites, but unilateral retrenchment in unemployment insurance, where recipients can be portrayed as "underserving".